Evaluation on mechanical properties of intra-ply hybrid carbon-aramid/epoxy composite laminates. (2018) - Ruban Rajasekar, B.; Asokan, R.; Senbagan, M.; Karthika, R.; sivajyothi, Kethavarapu; sharma, Nishtha
Abstract: This paper describes the mechanical behaviors of pure and hybrid composite laminate reinforced with carbon-aramid woven intra-ply fabrics using experimental investigation. The hybrid composite is a materialization of new property by intimate mixture combination using the superior mechanical properties of carbon fiber with the better impact material property of aramid fiber. Three types of laminate were considered for the present study such as aramid/epoxy, carbon/epoxy, and hybrid (carbon-aramid/epoxy). Composite laminates are investigated for their mechanical properties such as tensile strength, elastic modulus, flexural strength and flexural modulus. The carbon-aramid intra-ply exhibits the advantage of both the carbon and aramid composites. The fractography analysis was carried out to know the exact type of failures from the samples of failed specimen. The interfacial properties such as matrix cracks, fiber breakage, fiber pull-out and fracture were found out. The result indicated that hybrid/epoxy combination has improvised tensile strength as compared to aramid/epoxy and slightly lower than carbon/epoxy.